Surface patterning of a novel PEG‐functionalized poly‐l‐lactide polymer to improve its biocompatibility: Applications to bioresorbable vascular stents. Issue 3 (9th August 2018) - Pacharra, Sandra; Ortiz, Rocio; McMahon, Sean; Wang, Wenxin; Viebahn, Richard; Salber, Jochen; Quintana, Iban
Abstract: Today, research in the field of bioresorbable vascular stents (BVS) not only focusses on a new material being nontoxic but also tries to enhance its biocompatibility in terms of endothelialization potential and hemocompatibility. To this end, we used picosecond laser ablation technology as a single‐step and contactless method for surface microstructuring of a bioresorbable polymer which can be utilized in stent manufacture. The method works on all materials via fast material removal, can be easily adapted for micropatterning of tubular or more complex sample shapes and scaled up by means of micropatterning of metal molds for manufacturing. Here, picosecond laser ablation was applied to a bioresorbable, biologically inactive and polyethylene glycol‐modified poly‐L ‐lactide polymer (PEGylated PLLA) to generate parallel microgrooves with varying geometries. The different patterns were thoroughly evaluated by a series of cyto‐ and hemocompatibility tests revealing that all surfaces were non‐toxic and non‐hemolytic. More importantly, patterns with 20 to 25 µm wide and 6 to 7 µm deep grooves significantly enhanced endothelial cell adhesion in comparison to samples with smaller grooves. Here, human cardiac microvascular endothelial cells were found to align along the groove direction, which is thought to encourage endothelialization of intraluminal surfaces of BVS. © 2018 The Authors Journal of Biomedical Materials Research Part B: Applied Biomaterials Published by Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 00B: 000–000, 2018. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 107B: 624–634, 2019.